(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce the concept of cubic bipolar fuzzy subsemigroups and cubic bipolar fuzzy ideals in the context of semigroups. We explore their fundamental properties and examine how these structures interact within semigroups. The main thing this study adds is a way to describe weakly regular semigroups using the features of cubic bipolar fuzzy ideals. Through a detailed analysis, we establish several key results that highlight the role of these fuzzy ideals in understanding the algebraic structure of weakly regular semigroups.